We All Learned Together! Inclusive Science Activities With Parent Involvement in Preschool Classrooms - Aydin, Demet; Yilmaz Atman, Betul (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Parent-involved activities are critical in early childhood education as they offer children a range of learning experiences. This study examined parents' views on inclusive science activities implemented through parent involvement. Designed as a one-shot case study, the research was conducted in an inclusive preschool classroom in western T & uuml;rkiye, where 10 parents implemented inclusive science activities for children aged 5-6 years old with diverse developmental needs. The inclusive science activities were developed based on the Next Generation Science Standards and were conducted twice a week over 10 weeks with direct parent participation. Parents' views were collected using semi-structured interview forms, and the data were analyzed through content analysis. The findings revealed that parents held positive emotions and thoughts about inclusive science activities with parent involvement. After participating in the activities, parents reported conducting science activities at home and noted an increase in their knowledge of science concepts. Furthermore, parents observed that the activities facilitated their children's learning, fostered scientific curiosity and interest in science, and contributed to the development of their children's conceptual understanding of scientific phenomena. Based on these results, the study offers several implications for researchers and practitioners seeking to enhance science activities in inclusive preschool classrooms.
Keywords: Early childhood; inclusive education; inclusive science activities; parent involvement; science activities; SDG 4: Quality education; FAMILY INVOLVEMENT; ACHIEVEMENT; SCHOOL; HOME; STUDENTS; Education & Educational Research